Breaking boundaries female biblical interpreters who challenged the status quo - Calvert-Koyzis, Nancy; Weir, Heather E. (New York T & T Clark, 2010)
Women throughout the centuries have sought to break out of the constraints that their societies deemed appropriate for them. For interpreters in the Christian tradition, this often meant examining biblical texts that had been understood in ways that demeaned women
Includes bibliographical references and indexes. - Print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Feminist criticism; Bible -- Feminist criticism; Bible -- Feminist criticism -- Bible; Bible; Bible and feminism; Religion; RELIGION ; Biblical Reference ; Quotations; Feminist Criticism; Electronic books; Aufsatzsammlung